A Process for Evaluating Quality Decision-Making Practices During the Development, Review and Reimbursement of Medicines - Magdalena Bujar; Neil McAuslane; Stuart Walker; Sam Salek (Kerman University of Medical Sciences, 2022)
BackgroundThe development of a medicine is not only underpinned by good science but also by Quality DecisionMaking Practices (QDMPs). Indeed, it is important to ensure that all organisations involved in the lifecycle of medicines are aligning their practices in decision-making to the QDMPs to ensure quality, transparent and consistent decisionmaking processes.MethodsThe aim of this study was to evaluate the practicality of QoDoS (Quality of Decision-Making Orientation Scheme) in assessing the incorporation of ten QDMPs during the development, review and reimbursement of medicines, illustrated by case studies with a pharmaceutical company, a regulatory authority and a health technology assessment (HTA) agency. Individuals from each organisation completed the 47-item QoDoS questionnaire.ResultsThe results demonstrate the applicability of QoDoS in identifying favourable and unfavourable practices and in assessing the consistency and transparency of the QDMPs within each organisation, as well as across the different stakeholders. Furthermore, the study established the value of the methodology in raising awareness of the biases and best practices in decision-making, as well as having a basis for discussion for differences within and across stakeholders to promote consistency and alignment in decision-making. Finally, the QoDoS demonstrated the need for improvement across a number of decision-making practices for the 3 organisations such as the evaluation of alternatives and of the decision impact.ConclusionThe QoDoS can be used to benchmark organisations' decision-making practices to provide a basis for discussion to ultimately encourage a level of trust across and within organisations and helping to identify areas for improvement.